2015
DOI: 10.1177/1535370215588925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total gastrectomy on plasma silicon and amino acid concentrations in men

Abstract: The aim of the study was to determine one-year effects of total gastrectomy on plasma silicon and free amino acid concentrations in patients and evaluate changes of volumetric bone mineral density (vBMD) in lumbar spine. Eight patients were enrolled to the control (CTR) group. Six patients subjected to total gastrectomy (GX group) were included to the experimental group. vBMD in trabecular and cortical bone was measured in lumbar vertebrae at baseline (before surgery) and one year later using quantitative comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(44 reference statements)
0
4
0
1
Order By: Relevance
“…The carrageenan‐induced reduction in pepsin activities can have health ramifications because previous studies have demonstrated that the compromise in the activity and the amount of pepsin frequently causes protein digestion disorder (Bernert et al., 2007; Tatara et al., 2008). In addition, carrageenans also possess the ability for competitive inhibition of trypsin (Gatfield & Stute, 1972), a protease important for protein digestion in the duodenum, where approximately 50% of proteins are absorbed in humans (Tatara et al., 2015).…”
Section: Mechanisms By Which Carrageenans Exert Their Biological Effectsmentioning
confidence: 99%
“…The carrageenan‐induced reduction in pepsin activities can have health ramifications because previous studies have demonstrated that the compromise in the activity and the amount of pepsin frequently causes protein digestion disorder (Bernert et al., 2007; Tatara et al., 2008). In addition, carrageenans also possess the ability for competitive inhibition of trypsin (Gatfield & Stute, 1972), a protease important for protein digestion in the duodenum, where approximately 50% of proteins are absorbed in humans (Tatara et al., 2015).…”
Section: Mechanisms By Which Carrageenans Exert Their Biological Effectsmentioning
confidence: 99%
“…16 Finally, that Si can play an important role for bone wellbeing seems to be suggested also by a study in which gastrectomized male patients, at one year after surgery, found a significant reduction in volumetric BMD (measured by quantitative CT) in the lumbar spine (at both trabecular and cortical bone levels) compared to the control group, in association with an equally significant decrease in the plasma concentration of Si (also indicating, therefore, the importance of the exocrine and endocrine functions of the stomach in maintaining Si homeostasis). 17 Si, bone formation, and mineralization: In vitro and animal studies It has been suggested that Si may play a role in electrochemical bone mineralization processes, but the precise biological mechanism remains unclear at present. 1 In vitro studies have shown that this element stimulates the synthesis of type 1 collagen and osteoblastic 18 and increases the formation of mineralization nodules in mature osteoblast cultures.…”
Section: Impact Statementmentioning
confidence: 99%
“…Finally, that Si can play an important role for bone well-being seems to be suggested also by a study in which gastrectomized male patients, at one year after surgery, found a significant reduction in volumetric BMD (measured by quantitative CT) in the lumbar spine (at both trabecular and cortical bone levels) compared to the control group, in association with an equally significant decrease in the plasma concentration of Si (also indicating, therefore, the importance of the exocrine and endocrine functions of the stomach in maintaining Si homeostasis). 17…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have discussed the association between gastrectomy and decreased BMD in terms of malnutrition after gastrectomy and hormonal disorder [8, 9,13,14,22]. Some reports have focused on secondary hyperparathyroidism due to malabsorption of vitamin D and calcium as a cause of decreased BMD after gastrectomy [21,23] and others have focused on silicon, which is abundant in bones, skin, and other connective tissues [24][25][26]. Silicon is an important mineral required for bone formation, thus showing the importance of gastric exocrine and endocrine functions in the maintenance of silicon homeostasis.…”
Section: Discussionmentioning
confidence: 99%